Konsep Ummah dalam Tafsir Ibnu Katsir (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The word ummah generally means a group, community or nation united by religious beliefs and practices. In the Qur'an ummah has been mentioned 64 times in twenty-five surahs with two kinds of forms (singular and plural) and different meanings. The meaning of ummah is not limited to humans alone but is also used to refer to certain groups, such as religions, times, places or animals. The term is even used for a flock of birds, as in surah al-An'am (6): 38. In this meaning, it illustrates a new insight into the existence of brotherhood among humans in this world. Therefore, it is necessary to study more deeply to find out these meanings in tafsir ibnu katsir, because it is a classic tafsir patterned bil-ma'tsur, namely the interpretation of the Qur'an with the Qur'an, the interpretation of the Qur'an with hadith, the interpretation of the Qur'an with the words of the companions and tabi'in. This interpretation is critical and verification, with an emphasis on strict evaluation of the validity of the hadith sanad used. The explanation is comprehensive, covering linguistic, historical, and theological aspects, as well as providing a rich context through the causes of the revelation of the verse (asbabun nuzul). Ibn Kathir remains loyal to the principles of ahlus sunnah wal jamaah, maintains the purity of Islamic teachings, and integrates various disciplines in his interpretation, making this work the main reference in authentic and in-depth Qur'anic studies. This research is library research. The primary source is taken from Ibn Kathir's tafsir. Meanwhile, the secondary sources come from books, journals, scientific papers relevant to the theme of discussion.